Practical Solution for Effective Whole-Body Magnetic Fluid Hyperthermia Treatment. (13th December 2017) - Mamiya, Hiroaki; Takeda, Yoshihiko; Naka, Takashi; Kawazoe, Naoki; Chen, Guoping; Jeyadevan, Balachandran
Abstract : Magnetic fluid hyperthermia therapy is considered as a promising treatment for cancers including unidentifiable metastatic cancers that are scattered across the whole body. However, a recent study on heat transfer simulated on a human body model showed a serious side effect: occurrences of hot spots in normal tissues due to eddy current loss induced by variation in the irradiated magnetic field. The indicated allowable upper limit of field amplitude H a c for constant irradiation over the entire human body corresponded to approximately 100 Oe at a frequency f of 25 kHz. The limit corresponds to the value H a c f of 2.5 × 10 6  Oe·s −1 and is significantly lower than the conventionally accepted criteria of 6 × 10 7  Oe·s −1 . The present study involved evaluating maximum performance of conventional magnetic fluid hyperthermia cancer therapy below the afore-mentioned limit, and this was followed by discussing alternative methods not bound by standard frameworks by considering steady heat flow from equilibrium responses of stable nanoparticles. Consequently, the clarified potentials of quasi-stable core-shell nanoparticles, dynamic alignment of easy axes, and short pulse irradiation indicate that the whole-body magnetic fluid hyperthermia treatment is still a possible candidate for future cancer therapy.